2014
DOI: 10.1104/pp.114.236117
|View full text |Cite
|
Sign up to set email alerts
|

Additional Amphivasal Bundles in Pedicel Pith Exacerbate Central Fruit Dominance and Induce Self-Thinning of Lateral Fruitlets in Apple    

Abstract: Apple (Malus 3 domestica) trees naturally produce an excess of fruitlets that negatively affect the commercial value of fruits brought to maturity and impact their capacity to develop flower buds the following season. Therefore, chemical thinning has become an important cultural practice, allowing the selective removal of unwanted fruitlets. As the public pressure to limit the use of chemical agents increases, the control of thinning becomes a major issue. Here, we characterized the self-thinning capacity of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 74 publications
0
19
0
Order By: Relevance
“…The great number of shedded apple fruitlets has been reported by many authors and some studies have been conducted in attempt to determine an uniform and definite abscission pattern (Bangerth, 2000;Celton et al, 2014), but the clear and unequivocal answer, which fruitlets are predisposed to abscission remains unknown.…”
Section: The Hierarchy Of Positionsmentioning
confidence: 99%
“…The great number of shedded apple fruitlets has been reported by many authors and some studies have been conducted in attempt to determine an uniform and definite abscission pattern (Bangerth, 2000;Celton et al, 2014), but the clear and unequivocal answer, which fruitlets are predisposed to abscission remains unknown.…”
Section: The Hierarchy Of Positionsmentioning
confidence: 99%
“…An apple inflorescence contains four to six flowers; the number of fruitlets reaching maturity within an inflorescence depends, among other things, on pollination and genotype (Eccher et al ., ; Celton et al ., ). Fruit of important cultivars develops mostly on inflorescences formed on spurs (Butler, ; Forshey and Elfving, ).…”
Section: Introductionmentioning
confidence: 97%
“…Consequently, a hypothesis involving possible cross-talk between ROS metabolism and photosynthesis jointly regulating cotton leaf abscission is proposed. Our findings not only provide important insights into leaf shedding-associated changes induced by TDZ in cotton, but also highlight the possibility that the ROS and photosynthesis may play a critical role in the organ shedding process in other crops.Previous studies have found that ethylene accelerates organ abscission, while auxin inhibits this process [5][6][7][8][9]. Meanwhile, researchers have paid attention to the fact that multiple cell wall-degrading enzymes are activated to dissolve the cell wall and middle lamella of abscission zone, including cellulases, pecticlyases, polygalactosidases [10][11][12].…”
mentioning
confidence: 99%
“…Previous studies have found that ethylene accelerates organ abscission, while auxin inhibits this process [5][6][7][8][9]. Meanwhile, researchers have paid attention to the fact that multiple cell wall-degrading enzymes are activated to dissolve the cell wall and middle lamella of abscission zone, including cellulases, pecticlyases, polygalactosidases [10][11][12].…”
mentioning
confidence: 99%